The impact of loan acquisition on employees in the Mining Companies in Tarkwa- (A Case Study of Goldfields Ghana Limited) - Amarteyfio, Nicholas Quaye (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters In Business Administration,